Conference Review: OpenArch/IMTAL Sweden 2012 - Lynne Ashton (EXARC Journal, 2013)
As a long-standing member of IMTAL (International Museums Theatre Alliance – www.imtal-europe.org) I have always enjoyed their conferences. The workshops and participatory events are held in fantastic venues with theatrics to entertain and inform. However, this conference was being held in partnership with an archaeology group with delegates from around the world. Would they find our way of interpreting heritage too much to take?